Actual and perceived motor competence mediate the relationship between physical fitness and technical skill performance in young soccer players. - Duncan, M. J.; Eyre, E. L. J.; Noon, M. R.; Morris, R.; Thake, C. D.; Clarke, N. D.; Cunningham, A. J. (Journal of Australian Strength and Conditioning, 2020)
The importance of developing FMS has become a consideration in the development of soccer related talent in children. However, little attention has been paid to the importance of FMS in developing technical skills over an emphasis on enhancing physical fitness in coaching practice. This study examined the role of FMS and perceived competence in the relationship between physical fitness and technical skills in prepubescent soccer players.